Using an Atrial Fibrillation Decision Support Tool for Thromboprophylaxis in Atrial Fibrillation: Effect of Sex and Age. Issue 5 (May 2016) - Eckman, Mark H.; Lip, Gregory Y.H.; Wise, Ruth E.; Speer, Barbara; Sullivan, Megan; Walker, Nita; Kissela, Brett; Flaherty, Matthew L.; Kleindorfer, Dawn; Baker, Peter; Ireton, Robert; Hoskins, Dave; et al.
Abstract : Objectives: To assess the appropriateness of oral anticoagulant therapy (OAT) in women and elderly adults, looking for patterns of undertreatment or unnecessary treatment. Design: Retrospective cohort study. Setting: Primary care practices of an academic healthcare system. Participants: Adults (aged 28–93) with nonvalvular atrial fibrillation (AF) seen between March 2013 and February 2014 (N = 1, 585). Measurements: Treatment recommendations were made using an AF decision support tool (AFDST) based on projections of quality‐adjusted life expectancy calculated using a decision analytical model that integrates individual‐specific risk factors for stroke and hemorrhage. Results: Treatment was discordant from AFDST‐recommended treatment in 45% (326/725) of women and 39% (338/860) of men ( P  = .02). Although current treatment was discordant from recommended in 35% (89/258) of participants aged 85 and older and in 43% (575/1, 328) of those younger than 85 ( P  = .01), many undertreated elderly adults were receiving aspirin as the sole antithrombotic agent. Conclusion: Physicians should understand that female sex is a significant risk factor for AF‐related stroke and incorporate this into decision‐making about thromboprophylaxis. Treating older adults with aspirin instead of OAT exposes them to significant risk of bleeding with little to no reduction in AF‐related stroke risk.